Methylation and Chromatin Conformation of Adenovirus Type 12 DNA Sequences in Transformed Cells - Redfield, Jeanne Rosemary (My University, 1980)
The DNA blot hybridization technique was used to study the integrated adenovirus type 12 (Ad 12) DNA sequences in three cell lines established by transformation of baby rat kidney cells with the leftmost 16.5% of the Ad 12 genome. The cell lines 702-C1, 702-C2, and 702-C3 contained respectively 3 - 4, 9, and 4 copies of the DNA used for transformation, integrated at 1, 9, and 4 distinct sites in cellular DNA. Partial copies of the transforming fragment were detected at additional integration sites. Methylation of CCGG sequences at the viral integration sites was investigated, using the methylation-sensitive restriction endonuclease Hpa Il and its methylation-insensitive isoschizomer Msp I. In lines 702-C2 and 702-C3 some integrated copies of the viral DNA were methylated at all CCGG sequences while other copies were methylated at only some of these sequences. In line 702-C1 no viral CCGG sequences were methylated. Limited DNase I digestions of transformed cell nuclei were used to examine the chromatin conformation of the methylated and unmethylated viral DNA. A correlation was found between the absence of methylation at viral CCGG sequences in lines 702-C2 and 702-C3 and preferential cleavages by DNase I of the chromatin around these sequences. Results reported here suggest that these preferential DNase I cleavages occur at sites which are hypersensitive to DNase I. If so, the cleavages may be unrelated to the DNase I-sensitive nucleosome structure which has been associated with transcriptionally active genes.
Keywords: Biochemistry; Biochemistry